2017
DOI: 10.1080/15374416.2016.1266642
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Adolescent Cross-Informant Agreement in Clinically Referred Samples: Findings From Seven Societies

Abstract: To conduct international comparisons of parent-adolescent cross-informant agreement in clinical samples, we analyzed ratings on the Child Behavior Checklist (CBCL) and Youth Self-Report (YSR) for 6,762 clinically referred adolescents ages 11-18 from 7 societies (M = 14.5 years, SD = 2.0 years; 51% boys). Using CBCL and YSR data, we asked the following questions: (a) Do parents report more problems for their adolescent children than the adolescents report about themselves? (b) How do cross-informant correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 35 publications
5
23
0
4
Order By: Relevance
“…As would be expected, mean CBCL and YSR scores were much higher in these clinical samples than in the population samples (e.g., Total Problems scores means of 50.2 for the CBCL and 53.7 for the YSR, compared to 21.4 and 34.6, respectively, for the 25 population samples). Rescorla, Ewing et al (2016) reported mean parentadolescent cross-informant rs of .41 for Total Problems and .47 for Internalizing, very similar to those Rescorla et al (2013) found for population samples (both .45). However, the mean r for Externalizing of .55 was larger than that reported for population samples (.46).…”
Section: Cross-cultural Perspectives On Agreement Regarding Adolescensupporting
confidence: 62%
See 4 more Smart Citations
“…As would be expected, mean CBCL and YSR scores were much higher in these clinical samples than in the population samples (e.g., Total Problems scores means of 50.2 for the CBCL and 53.7 for the YSR, compared to 21.4 and 34.6, respectively, for the 25 population samples). Rescorla, Ewing et al (2016) reported mean parentadolescent cross-informant rs of .41 for Total Problems and .47 for Internalizing, very similar to those Rescorla et al (2013) found for population samples (both .45). However, the mean r for Externalizing of .55 was larger than that reported for population samples (.46).…”
Section: Cross-cultural Perspectives On Agreement Regarding Adolescensupporting
confidence: 62%
“…An important pattern noted in some clinical samples is that when adolescents' ratings yielded clinically elevated scores, most parents were in agreement, but when adolescents' ratings did not yield clinically elevated scores, less than half of parents were in agreement (e.g., Martin et al 2004). Rescorla, Ewing et al (2016) used CBCL and YSR data for 6,762 clinically referred adolescents ages 11-18 from seven different societies in order to conduct systematic cross-cultural comparisons of parent-adolescent agreement in clinical samples parallel to those reported by Rescorla et al (2013) for population samples. Although mean YSR scores in population samples were higher than mean CBCL scores for all problem scales in almost all societies, mean differences between the YSR and CBCL in these seven clinical samples were small, often non-significant, and inconsistent in direction.…”
Section: Cross-cultural Perspectives On Agreement Regarding Adolescenmentioning
confidence: 99%
See 3 more Smart Citations